UNLOCKING THE POTENTIAL OF QUALITATIVELY ORIENTED MIXED METHODS RESEARCH - N. Poth, Cheryl (2025)
The growing recognition of mixed methods research as a valuable approach to understanding our complex world, along with the emergence of hybrid designs, presents opportunities for prioritizing qualitative integration. Integration, the defining feature of mixed methods research, requires intentional and strategic efforts to generate novel insights by combining qualitative and quantitative approaches in various ways. In qualitatively oriented designs, integration plays a critical role in preserving and amplifying qualitative contributions, yet little guidance exists for researchers. While qualitatively oriented mixed methods research is widely recognized within the broader mixed methods field, defining its distinct niche remains underexplored. This paper, based on a keynote presented in the online component of the 9th World Conference on Qualitative Research, sheds light on the often overlooked potential of mixed methods designs that prioritize qualitative perspectives in their integration with quantitative research approaches. Central to our exploration is the fundamental question: What guides the design of qualitatively oriented mixed methods research? To that end, we examine the application of key mixed methods practices to help researchers bring integration to the forefront of their qualitatively oriented mixed methods designs. Using compelling examples and describing practical strategies, we provide guidance on leveraging qualitatively oriented mixed methods research as a distinct and valuable approach— enhancing methodological rigour and integration evidence. Researchers benefit from practical guidance, ensuring that the unique strengths of qualitative inquiry are both elevated and enhanced in mixed methods designs. Together, we unlock the potential of qualitatively oriented mixed methods to navigate and understand our intricately woven world.